2007
DOI: 10.1007/s12264-007-0038-6
|View full text |Cite
|
Sign up to set email alerts
|

Observation of amyloid precursor protein cleavage and Aβ generation in living cells by using multiphoton laser scanning microscopy

Abstract: Objective To investigate the proteolytic mechanism of amyloid precursor protein (APP) and to explore amyloidbeta (A ) generation in living neurons. Methods DNA fragments were amplified by PCR or synthesized. The four fragments, CFP, 54bp, YFP and C99 were ligated into pcDNA3.0 vector to construct the recombinant plasmids pcDNA3.0-CFP-54bp-YFP and pcDNA3.0-CFP-54bp-YFP-C99. The SH-SY5Y cells were transiently transfected with pcDNA3.0-CFP-54bp-YFP or pcDNA3.0-CFP-54bp-YFP-C99. The expression of fusion gene was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Very interestingly, recent studies from our group also demonstrated that BR297 efficiently improved neuroblastoma cell bioenergetics by increasing the cellular ATP level and mitochondrial respiration under normal/physiological situations . Consistently, BR297 treatment, which reduced ROS levels, as well as ameliorated mitochondrial respiration and cell survival, was also more effective than AP with respect to preventing oxidative stress‐evoked death of the APP‐transfected neuroblastoma cells that represent a relevant and reliable cell model for the investigation of physio‐pathological mechanisms involved in AD . We have also found that our 3α‐analogue BR351 (O‐allyl‐AP), which strongly promoted the proliferation and protection of neural stem cells against β‐amyloid‐induced death, only slightly stimulated mitochondrial activities .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Very interestingly, recent studies from our group also demonstrated that BR297 efficiently improved neuroblastoma cell bioenergetics by increasing the cellular ATP level and mitochondrial respiration under normal/physiological situations . Consistently, BR297 treatment, which reduced ROS levels, as well as ameliorated mitochondrial respiration and cell survival, was also more effective than AP with respect to preventing oxidative stress‐evoked death of the APP‐transfected neuroblastoma cells that represent a relevant and reliable cell model for the investigation of physio‐pathological mechanisms involved in AD . We have also found that our 3α‐analogue BR351 (O‐allyl‐AP), which strongly promoted the proliferation and protection of neural stem cells against β‐amyloid‐induced death, only slightly stimulated mitochondrial activities .…”
Section: Discussionsupporting
confidence: 68%
“…Because the key neuroendocrine and neuroactive neurosteroid AP exerts pleiotropic actions, including cell proliferation-promoting, neurogenic and neuroprotective effects, its use in the development of targeted therapeutic strategies remains complex. [4][5][6][7][8][9][10][11][12][13][14][15][16]23,35,36,56,57 Therefore, we decided to synthesise AP analogues with the aim of identifying compounds that may have higher efficacy and/or better [65][66][67][68][69][70] We have also found that our 3αanalogue BR351 (O-allyl-AP), which strongly promoted the proliferation and protection of neural stem cells against β-amyloid-induced death, only slightly stimulated mitochondrial activities. 58,71 Therefore, it appears that the subtle structural difference between BR351 and BR297 is sufficient to generate selective activity profiles allowing the possibility of developing a BR351-or BR297-based therapeutic strategy adapted to the pathological conditions that require either neurogenic and neuroprotective effects or only a selective action to protect nerve cells against death without promoting cell proliferation.…”
Section: Discussionmentioning
confidence: 99%